A longitudinal comparison of information literacy in students starting Politics degrees. Issue 2 (1st June 2019) - Thornton, Stephen
Abstract : Information literacy, the concept most associated with inculcating the attributes necessary to behave in a strategic, thoughtful and ethical manner in the face of a superfluity of information, has been part of the information specialist scene for many years. As the United Kingdom's QAA benchmark statements for Politics and International Relations highlight, many of the competences associated with this concept are vital in the honourable struggle to become a successful graduate of those disciplines. This article presents a longitudinal study of a survey used to expose the information literacy levels of two groups of first-year Politics/IR students at a British university and, using the logic of 'most similar design', make informed inferences about the level of students' information literacy on coming into tertiary education.